Lights, camera -- cats! - Keene, Carolyn (Nancy Drew and the Clue Crew ;, 2007)
Nancy, Bess, and George visit the Hollywood set of the movie "The Aliens Next Door", and try to solve the mystery of the missing leading cat star, Fluffington.